Prototype of Automatic Goods Moving Equipment to Multi-storey Floor with Arduino - Alakhyar, Farisqi Yusuf; Mushlihudin, Mushlihudin (Association for Scientific Computing Electrical and Engineering (ASCEE), 2020)
The industrial world is currently growing and has become an important part of the world as a whole. An example is the process of grouping and moving goods over and over in the warehouse located on the upper floor becomes a problem if the process is still done manually. So shipping the goods requires a lot of energy needed and is still less efficient. This research made a prototype design of a freight elevator that can place goods automatically in a multi-storey floor storage warehouse, aiming to facilitate the performance of the arrangement of goods during the delivery process to the upper floor. The hardware consists of an Arduino Mega 2560 microcontroller, two 12 volt dc motors, an infrared sensor and a limit switch. Testing this system uses a package of goods from cardboard media, with a package thickness of 0.2 cm. The results of the testing of the classification of tool goods packages can work well so as to improve work effectiveness with the accuracy of the success of the tool in placing goods to 3 floors in sequence with an accuracy of 86.7%, then the placement of goods with 1 empty space 98.9% accuracy, and placement goods with 2 combined empty spaces are 84.47%.